The Social Worker as Representative of the State or Society: Sipho’s Story (Journal of Comparative Social Work, 2007)
All social workers must determine to whom is their primary responsibility held - the client or the state. This paper explores issues that surround this question. The context is the criminal justice system in South Africa. A case is taken, the story of Jason as a vehicle to explore these issues.